2001
DOI: 10.1063/1.1347965
|View full text |Cite
|
Sign up to set email alerts
|

Resolution limits for infrared microspectroscopy explored with synchrotron radiation

Abstract: The spatial resolution for infrared microspectroscopy is investigated to determine the practical limits imposed by diffraction or optical aberrations. Quantitative results are obtained using high brightness synchrotron radiation, which serves as a diffraction-limited infrared “point source” for the microscope. The measured resolving power is in good agreement with diffraction theory, including a ∼ 30% improvement for a confocal optical arrangement. The diffraction calculation also shows how the confocal setup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
184
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(186 citation statements)
references
References 8 publications
2
184
0
Order By: Relevance
“…The lateral resolution predicted by the diffraction limit would be ∼10 µm at a wavelength of 10 µm if the measurement was carried out confocally, but with an aperture of 10 µm, the light throughput would be compromised for the PE300 instrument. However, confocal IR-MSP measurements have been reported using synchrotron-based IR-MSP (Carr, 2001). …”
Section: F Diffraction Limit and Spatial Resolutionmentioning
confidence: 99%
“…The lateral resolution predicted by the diffraction limit would be ∼10 µm at a wavelength of 10 µm if the measurement was carried out confocally, but with an aperture of 10 µm, the light throughput would be compromised for the PE300 instrument. However, confocal IR-MSP measurements have been reported using synchrotron-based IR-MSP (Carr, 2001). …”
Section: F Diffraction Limit and Spatial Resolutionmentioning
confidence: 99%
“…Infrared reflectance micro-spectroscopy between 150 and 6000 cm -1 was performed at beamline U12IR at the National Synchrotron Light Source, Brookhaven National Laboratory [39]. Infrared polarizers were employed to obtain reflectance spectra parallel and perpendicular to the long axis of the crystals, i.e.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] However, spatial resolution in transmission mode is lower than that of micro-ATR mode even when measured using a powerful synchrotron source. [25][26] Although a recent report 27 has shown that, by using a multi-beam synchrotron source and a high magnifying power objective, the spatial resolution in transmission mode can approach that of micro-ATR mode.…”
Section: Introductionmentioning
confidence: 99%